2014
DOI: 10.1016/j.ijchv.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Repair or prosthesis insertion in ischemic mitral regurgitation: Two faces of the same medal

Abstract: ObjectiveThe proper treatment of chronic ischemic mitral regurgitation (CIMR) is still under evaluation. The different role of mitral valve repair (MVr) or mitral valve prosthesis insertion (MVPI) is still not defined.MethodsFrom May 2009 to December 2011 167 patients with ejection fraction (EF) ≤ 40% had MV surgery for CIMR, MVr in 135 (80.8%) and MVPI in 32 (19.2%). Indication to MVPI was a MV coaptation depth > 10 mm. EF was lower (26 ± 7 vs 32 ± 6, p = 0.0000) in MVPI, whereas MR grade (3.6 ± 0.8 vs 2.7 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The included surgical studies mainly used annuloplasty for MV repair ( 20 22 ). Several studies additionally reported chordal cutting ( 23 ), chordal replacement ( 21 ), papillary muscle relocation ( 20 , 24 ) or left ventricular remodeling ( 24 , 25 ). Only one study explicitly reported edge-to-edge repair in combination with annuloplasty ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included surgical studies mainly used annuloplasty for MV repair ( 20 22 ). Several studies additionally reported chordal cutting ( 23 ), chordal replacement ( 21 ), papillary muscle relocation ( 20 , 24 ) or left ventricular remodeling ( 24 , 25 ). Only one study explicitly reported edge-to-edge repair in combination with annuloplasty ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has to be mentioned that MV surgery often comprises different treatment strategies like sternotomy or minimally invasive access, additional subvalvular treatment or ventricular remodeling such as chordal cutting/replacement ( 21 , 23 ), edge-to-edge repair ( 29 ) or papillary muscle approximation ( 20 , 24 ). Moreover, concomitant procedures like coronary artery bypass graft, tricuspid valve repair, Maze procedures or pulmonary vein isolation and left atrial appendage occlusion are frequently performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MV surgery frequently includes several treatment modalities, such as sternotomy or minimally invasive access, further subvalvular therapy, or ventricular remodeling, such as chordal cutting/replacement [ 14 , 15 ], edge‐to‐edge repair [ 16 ], or papillary muscle approximation [ 17 , 18 ]. Additionally, simultaneous treatments like a tricuspid valve repair, coronary artery bypass graft, pulmonary vein isolation, maze procedures or pulmonary vein isolation, or a left atrial appendage occlusion are commonly carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Mitral valve repair is generally preferred whenever possible based on valve pathology and patient stability: it avoids longterm anticoagulation, decreases infective endocarditis risk, and provides greater leaflet durability. Among repairs, different techniques are available, but annuloplasty with prosthetic ring is the gold standard [41,42]. On the other hand, valve replacement is usually reserved for situations where the valve cannot be reasonably repaired, or when repair is unlikely to be tolerated clinically.…”
Section: Ischaemic Mitral Regurgitationmentioning
confidence: 99%